Are there potential safety problems concerning the use of electronic performance-tracking systems? The experience of a multisport elite club - Medina, D.; Pons, E.; Gomez, A.; Guitart, M.; Martin, A.; Vazquez-Guerrero, J.; Camenforte, I.; Carles, B.; Font, R. (International Journal of Sports Physiology and Performance, 2017)
Despite approval of the use of electronic performance-tracking systems (EPTSs) during competition by the International Football Association Board, other team-sport organizations and leagues have banned their use due to "safety concerns," with no evidence to support this assertion. The aim of the current brief report was to provide empirical evidence to support the widespread use of EPTSs across all sports by examining safety issues concerning their use in a multi-team-sport club. Five outdoor football teams (1st team, 2nd team, under 19 [U-19], under 18 [U-18], and 1st team female) and 3 indoor-sport (basketball, futsal, and handball) teams were monitored, accounting for a total of 63,734 h of training and 12,748 h of game time. A questionnaire was sent to all fitness coaches involved, and the clinical history was reviewed for every medical issue reported. Six minor chest contusions were recorded in female football goalkeepers wearing the frontal chest strap (3.17 episodes per 1000 training h). During training, 3 episodes of minor skin abrasion affecting the thoracic area due to wearing vests too tight were recorded in the U-19 football team (0.21 per 1000 h) and 2 episodes in U-18 (0.39 per 1000 h). It must be noted that none of these episodes resulted in lost days of training or games, and none required medical assistance. In conclusion, empirical evidence confirms that EPTSs are safe to use across team sports.